ODD HARMONIOUS LABELING ON SOME STRING GRAPH CLASSES - Firmansah, Fery (PATTIMURA UNIVERSITY, 2022)
A graph with the labeling properties of odd harmonic is called an odd harmonious graph. The purpose of this research was to get labeling properties of odd harmonic on the class of string graphs. The research used was a qualitative research method. The result of the research was that the definition and construction of a string graph, the union of a string graph, and the multiple string graph are obtained. Furthermore, it has been proved that a string graph, the union of a string graph, and the multiple string graph is an odd harmonious graph.